Paddy Clarke : ha ha ha - Doyle, Roddy, 1958- (London : Vintage, 1998)
Patrick Clarke is ten and wants to get out of the Corporation housing and become a missionary like Father Damien. Before he can, he needs to decipher some of the things he sees and to understand more about people and what motivates them.
Adult.
Booker Prize, 1993
Keywords: Children -- Fiction; Company towns -- Fiction; Friendship -- Fiction; Children -- Fiction; Cities and towns -- Fiction; Friendship -- Fiction